Cardiac risk in recovered Covid-19 patients evaluated by 123I-mIBG - Alessandro Liebich; Gabriel Sheikh; Ralph. A. Bundschuh; Malte Kircher; Alexander Dierks; Bernd Nittbaur; Philip Raake; Maximilian Rieger; Takahiro Higuchi; Christian H. Pfob; Constantin Lapa (Scientific Reports)
Abstract To determine whether cardiac sympathetic nervous dysfunction is present, in this single center prospective, non-randomized trial non-invasive SPECT/CT imaging using the radiotracer 123I-metaiodobenzylguanidine was performed in 33 recovered COVID-19 patients without pre-existing cardiac conditions. Increased cardiac sympathetic activity, as indicated by late HMR, was observed in 67.7% of patients. At 6–8 months, 82% of these subjects (27/33) received follow-up, and cardiac sympathetic innervation abnormalities were still present in 70.4% (19/27). Additionally, at 12–15 months post-diagnosis, persistently abnormal HMRs were found in 9 individuals who initially had abnormal sympathetic innervation. Further follow-up is needed to investigate potential long-term cardiovascular consequences of COVID-19.